Bushido and the art of living an inquiry into samurai values - Bennett, Alexander (Japan Publishing Industry Foundation for Culture, 2017)
"What is Bushido? What is Budo? How are the culture and traditions of the samurai connected with the modern martial arts? Is the ancient wisdom of Japan's feudal warriors truly relevant in the twenty-first century? If so, how can it be accessed? This book addresses these questions, and is a must read not only for martial artists, but also for those who want to know more about the enigmatic Japanese mind and notions of self-identity"--Back cover.